Fundamental q, Cash Flow, and Investment: Evidence from Farm Panel Data - Bierlen, Ralph; Featherstone, Allen M. (The Review of Economics and Statistics, 1998)
This study used a 1976–1992 panel data set to test whether farm machinery investors face finance constraints. Tests were based on fundamental q investment equations in which cash flow was added as an additional explanatory variable. Results indicated that (1) credit constraints were generally not a problem during the 1970s boom, (2) credit constraints became a problem during the 1980s and early 1990s because of tighter credit and/or more conservative financial managerial styles, (3) the investment-cash flow relationships of low-debt and older-operator farms were not significantly affected by farm business cycles, and (4) the investment-cash flow relationships of high-debt and young-operator farms were affected strongly by business cycles. Debt level was the strongest determinant of credit constraints; asset size and operator age were less important.